Solvent exfoliation stabilizes TiS2 nanosheets against oxidation, facilitating lithium storage applications - Vega-Mayoral, Victor; Backes, Claudia (Nanoscale, 2019)
Titanium disulfide is a promising material for a range of applications, including lithium-ion battery (LIB) anodes. However, its application potential has been severely hindered by the tendency of exfoliated TiS2 to rapidly oxidize under ambient conditions. Herein, we confirm that, although layered TiS2 powder can be exfoliated by sonication in aqueous surfactant solutions, the resultant nanosheets oxidise almost completely within hours. However, we find that upon performing the exfoliation in the solvent cyclohexyl-pyrrolidone (CHP), the oxidation is almost completely suppressed. TiS2 nanosheets dispersed in CHP and stored at 4 °C in an open atmosphere for 90 days remained up to 95% intact. In addition, CHP-exfoliated nanosheets did not show any evidence of oxidation for at least 30 days after being transformed into dry films even when stored under ambient conditions. This stability, probably a result of a residual CHP coating, allows TiS2 nanosheets to be deployed in applications. To demonstrate this, we prepared lithium ion battery anodes from nano : nano composites of TiS2 nanosheets mixed with carbon nanotubes. These anodes displayed reversible capacities (920 mA h g−1) close to the theoretical value and showed good rate performance and cycling capability.
Im Titel ist die Zahl 2 tiefgestellt
Gesehen am 13.05.2019